Total Rhythm in Three Dimensions Towards a Motional Theory of Melodic Dance Rhythm in Swedish Polska Music - Kaminsky, David (Edinbugh: Edinbugh University Press, 2014)
RESUMEN: In this article I present an ethnotheory of the music/dance relationship in Swedish polska, based on dance fieldwork and interviews I have conducted with polska dance musicians. I discuss three mechanisms that these musicians use to communicate movement patterns to dancers: iteration (entrainment via repetition), metaphor (timbral weight conveying motional weight), and sympathy (musician's movements mapping dance movements). I then discuss how musicians use these mechanisms to control four motional parameters: pulsation (rate and consistency of tempo), lean (degree and direction of tilt over the dance axis) viscosity (level of perceived air resistance), and libration (degree and timing of vertical motion). The work is intended in part as a case study of how theories of both music and dance can benefit from a focused analysis of the relationship between those two domains, as well as how studies of music/dance relations can benefit from the application of ethnographic research techniques.